Simple and scalable preparation of reduced graphene oxide-silver nanocomposites via rapid thermal treatment - Zainy, M.; Huang, N.M.; Kumar, S.V.; Lim, H.N.; Chia, C.H.; Harrison, I. (2012)
In this study, we describe a simple, straightforward and scalable method for the preparation of high purity reduced graphene oxide/silver (rGO/Ag) nanocomposites via a rapid thermal reduction method. Silver acetate (AgCH3O2) was used as a silver precursor and graphene oxide (GO) served as a substrate for the Ag nanoparticles. The nanocomposites were prepared by grinding GO and the silver precursor, and were rapidly treated at 1000 degrees C in a furnace for 20s under an ambient atmosphere. The obtained rGO/Ag nanocomposites were confirmed by ultraviolet-visible spectroscopy (UV-vis), X-ray diffraction (XRD), and Raman spectroscopy. field emission scanning electron microscope (FESEM) and transmission electron microscope (TEM) images showed uniformly distributed Ag nanoparticles on the reduced GO surface. The average particle size of the formed Ag nanoparticles was 16.9 +/- 3.5 nm. Since the preparation method does not involve any addition of a surfactant or stabilizer, the obtained nanocomposites are of high purity.